2016
DOI: 10.1073/pnas.1603531113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transcriptional pausing through the secondary channel of RNA polymerase

Abstract: Transcriptional pausing has emerged as an essential mechanism of genetic regulation in both bacteria and eukaryotes, where it serves to coordinate transcription with other cellular processes and to activate or halt gene expression rapidly in response to external stimuli. Deinococcus radiodurans, a highly radioresistant and stressresistant bacterium, encodes three members of the Gre family of transcription factors: GreA and two Gre factor homologs, Gfh1 and Gfh2. Whereas GreA is a universal bacterial factor tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 63 publications
(118 reference statements)
2
26
0
Order By: Relevance
“…On the whole, our data demonstrate that Gfh factors act on a variety of paused transcription complexes, including elemental, hairpin‐dependent, post‐translocated, backtracking‐dependent, and consensus pauses, which significantly differ in their structures and translocation registers of the RNAP active site. At the same time, Dra Gfh factors have little effect on the rate of nucleotide addition in nonpaused catalytically active TECs . Previous studies suggested that Gfh factors recognize and stabilize a specific ratcheted conformation of RNAP .…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…On the whole, our data demonstrate that Gfh factors act on a variety of paused transcription complexes, including elemental, hairpin‐dependent, post‐translocated, backtracking‐dependent, and consensus pauses, which significantly differ in their structures and translocation registers of the RNAP active site. At the same time, Dra Gfh factors have little effect on the rate of nucleotide addition in nonpaused catalytically active TECs . Previous studies suggested that Gfh factors recognize and stabilize a specific ratcheted conformation of RNAP .…”
Section: Resultsmentioning
confidence: 82%
“…). As our previous study suggested that Gfh factors do not act on backtracked TECs (in particular, they cannot compete with GreA in such complexes) , Gfh1 probably stimulates the initial step of pausing preceding RNAP backtracking .…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations